Tumor Necrosis Factor in Traumatic Brain Injury: Effects of Genetic Deletion of p55 or p75 Receptor. Issue 8 (August 2013) - Longhi, Luca; Perego, Carlo; Ortolano, Fabrizio; Aresi, Silvia; Fumagalli, Stefano; Zanier, Elisa R; Stocchetti, Nino; De Simoni, Maria-Grazia
The role of tumor necrosis factor (TNF) and its receptors after traumatic brain injury (TBI) remains unclear. We evaluated the effects of genetic deletion of either p55 or p75 TNF receptor on neurobehavioral outcome, histopathology, DNA damage and apoptosis-related cell death/survival gene expression (bcl-2/bax), and microglia/macrophage (M/M) activation in wild-type (WT) and knockout mice after TBI. Injured p55 (– / –) mice showed a significant attenuation while p75 (– / –) mice showed a significant worsening of sensorimotor deficits compared with WT mice over 4 weeks postinjury. At the same time point, contusion volume in p55 (– / –) mice (11.1 ± 3.3 mm 3 ) was significantly reduced compared with WT (19.7 ± 3.4 mm 3 ) and p75 (– / –) mice (20.9 ± 3.2 mm 3 ). At 4 hours postinjury, bcl-2/bax ratio mRNA expression was increased in p55 (– / –) compared with p75 (– / –) mice and was associated with reduced DNA damage terminal deoxynucleotidyl transferaseYmediated dUTP nick end labeling (TUNEL-positivity), reduced CD11b expression and increased Ym1 expression at 24 hours postinjury in p55 (– / –) compared with p75 (– / –) mice, indicative of a protective M/M response. These data suggest that TNF may exacerbate neurobehavioral deficits and tissue damage via p55 TNF receptor whose inhibition may represent a specific therapeutic target after TBI.